The Social Impact of a WTO Agreement in Indonesia - Robilliard, Anne-Sophie; Robinson, Sherman (World Bank, Washington, DC, 2012)
Indonesia experienced rapid growth and the expansion of the formal financial sector during the last quarter of the 20th century. Although this tendency was reversed by the shock of the financial crisis that spread throughout Asia in 1997 and 1998, macroeconomic stability has since then been restored, and poverty has been reduced to pre-crisis levels. Poverty reduction remains nevertheless a critical challenge for Indonesia with over 110 million people (53 percent of the population) living on less than $2 a day. The objective of this study is to help identify ways in which the Doha Development Agenda might contribute to further poverty reduction in Indonesia. To provide a good technical basis for answering this question, the authors use an approach that combines a computable general equilibrium (CGE) model with a microsimulation model. This framework is designed to capture important channels through which macroeconomic shocks affect household incomes. It allows making recommendations on specific trade reform options as well as on complementary development policy reforms. The framework presented in this study generates detailed poverty outcomes of trade shocks. Given the magnitude of the shocks examined here and the structural features of the Indonesian economy, only the full liberalization scenario generates significant poverty changes. The authors examine their impact under alternative specifications of the functioning of labor markets. These alternative assumptions generate different results, all of which confirm that the impact of full liberalization on poverty would be beneficial, with wage and employment gains dominating the adverse food price changes that could hurt the poorest households. Two alternative tax replacement schemes are examined. While direct tax replacement appears to be more desirable in terms of efficiency gains and translates into higher poverty reduction, political and practical considerations could lead the Government of Indonesia to choose a replacement scheme through the adjustment of value-added tax rates across nonexempt sectors.